PELATIHAN SISTEM INFORMASI AKUNTANSI UNTUK MENINGKATKAN LITERASI KEUANGAN DI UMKM DAPUR OMA RETHA - Apriliandani, Cut Tia; Afriyanti, Reni; Apriyatin, Hidup; Makapuan, Siska Theresiana; Rahmadi, Zara Tania; Setiawan, Indra (ASOSIASI IDEBAHASA KEPRI, 2025)
This research addresses the critical issue of financial literacy among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, specifically through the implementation of accounting information systems, with a focus on the case study of Dapur Oma Retha. The selection of this topic is driven by the significant challenges faced by MSMEs in managing their finances effectively, which often hinders their growth and sustainability. The study employs a Mixed Methods approach, combining both quantitative and qualitative research methods. It begins with surveys and in-depth interviews to identify the financial management issues encountered by the participants. Following this, theoretical training on financial statements and technical guidance in using Microsoft Excel are provided to enhance participants' skills. Direct mentoring sessions are also conducted to assist participants in preparing their financial reports accurately. The findings reveal that the proper application of accounting practices significantly improves participants' understanding of their business's financial health and facilitates more informed decision-making. This research underscores the necessity for government support in the form of policies and funding for training and mentoring programs aimed at MSMEs, thereby enhancing their financial management capabilities. Ultimately, the study highlights the importance of improving financial literacy as a means to foster the development and competitiveness of MSMEs in the market.